PEMANFAATAN TEKNOLOGI WEBSITE INFORMASI BAGI SMART SDM PONDOK PESANTREN SIRAJUL MUSTHAFA SILAU LAUT - Nuriadi Manurung; Herman Saputra; Elly Rahayu; Roesella Anjani (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2023)
Abstract: The Sirajul Musthafa Silau Laut Islamic Boarding School is a religious educational institution that has a big mission of producing a young generation with noble character and broad insight. This Islamic boarding school has a long history of spreading Islamic values and forming strong characters in its students. As time goes by, the Sirajul Musthafa Islamic Boarding School realizes the importance of adapting to information and communication technology (ICT) to increase efficiency and effectiveness in managing information and equip its students with technological skills. Utilization of the Information System as a form of seriousness at the Sirajul Musthafa Islamic Boarding School, Asahan Regency in conveying information regarding academic and non-academic activities within the Islamic Boarding School and Asahan Regency as a form of readiness in the digital world that all information can be accessed online. Apart from that, the Sirajul Musthafa Islamic Boarding School also participates in improving the quality of education in the modern era, of course, it requires information media such as websites to provide up-to-date information as a form of concern and a form of good performance that can be accessed by the community around Asahan Regency, so that it can build community trust in entrusting their children to the Sirajul Musthafa Islamic Boarding School. The result of this activity is the development of the Sirajul Musthafa Islamic Boarding School Website as an information system media and the implementation of HR training to improve HR capabilities. Keyword: information;system;website. Abstrak: Pondok Pesantren Sirajul Musthafa Silau Laut merupakan sebuah lembaga pendidikan agama yang memiliki misi besar dalam mencetak generasi muda yang berakhlak mulia dan berwawasan luas. Pondok pesantren ini memiliki sejarah panjang dalam menyebarkan nilai-nilai keislaman dan membentuk karakter yang tangguh pada para santrinya. Seiring dengan perkembangan zaman, Pondok Pesantren Sirajul Musthafa Silau Laut menyadari pentingnya beradaptasi dengan teknologi informasi dan komunikasi (TIK) guna meningkatkan efisiensi dan efektivitas dalam pengelolaan informasi serta membekali santrinya dengan keterampilan teknologi. Pemanfaatan Sistem Informasi sebagai bentuk keseriusan Pondok Pesantren Sirajul Musthafa Silau Laut Kabupaten Asahan dalam menyampaikan informasi mengenai kegiatan akademik dan non-akademik dilingkungan Pondok Pesantren maupun Kabupaten Asahan sebagai bentuk kesiapan dalam dunia digital bahwa segala informasi dapat diakses secara online. Selain itu juga Pondok Pesantren Sirajul Musthafa Silau Laut ikut serta dalam peningkatan kualitas pendidikan dalam era modern tentunya membutuhkan media informasi seperti website untuk menyediakan informasi yang up to date sebagai bentuk kepedulian dan bentuk kinerja yang baik yang dapat diakses oleh masyarakat sekitar Kabupaten Asahan, sehingga dapat membangun kepercayaan Masyarakat dalam menitipkan anaknya di Pondok Pesantren Sirajul Musthafa. Hasil dari kegiatan ini adalah terbangunya Website Pondok Pesantren Sirajul Musthafa sebagai media sistem informasi dan terlaksannya pelatihan SDM  untuk meningkatan kemampuan SDM. Kata kunci: informasi;sistem;website.